2022
DOI: 10.3389/fpsyt.2022.991753
|View full text |Cite
|
Sign up to set email alerts
|

A proposed mechanism for the MDMA-mediated extinction of traumatic memories in PTSD patients treated with MDMA-assisted therapy

Abstract: Post-traumatic stress disorder (PTSD) is a devastating psychiatric disorder afflicting millions of people around the world. Characterized by severe anxiety, intrusive thoughts, pervasive nightmares, an assortment of somatic symptoms, associations with severe long-term health problems, and an elevated risk of suicide, as much as 40–70% of patients suffer from refractory disease. 3,4-Methylenedioxy-methamphetamine (MDMA), like classic psychedelics such as psilocybin, have been used to enhance the efficacy of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…A study examining the effects of stress and positive emotions on vaccine response revealed that individuals with a positive emotional style had significantly higher levels of antibodies post-vaccination, with a p-value of 0.02 and an effect size of 0.47. This finding suggests that psychological factors can modulate the immune system's response to vaccines [16][17] .This laboratory-based evidence underscores the impactful role of psychological suggestion in modulating the immune system's response to vaccines. The observed correlation between positive emotional states and enhanced antibody production provides a tangible link between psychological factors and physiological outcomes.…”
Section: Psychological Suggestion In Immune Responsementioning
confidence: 64%
“…A study examining the effects of stress and positive emotions on vaccine response revealed that individuals with a positive emotional style had significantly higher levels of antibodies post-vaccination, with a p-value of 0.02 and an effect size of 0.47. This finding suggests that psychological factors can modulate the immune system's response to vaccines [16][17] .This laboratory-based evidence underscores the impactful role of psychological suggestion in modulating the immune system's response to vaccines. The observed correlation between positive emotional states and enhanced antibody production provides a tangible link between psychological factors and physiological outcomes.…”
Section: Psychological Suggestion In Immune Responsementioning
confidence: 64%
“…This review suggests conceptual and methodological ways in which future studies can overcome current barriers and shed light on the specific roles of these limbic subregions in posttraumatic psychopathology. Consequently, these efforts may pave the way for novel therapeutic strategies for PTSD prevention and treatment ( 132 , 133 , 134 ).…”
Section: Discussionmentioning
confidence: 99%
“…By upregulating BDNF, MDMA may stimulate neuroplasticity and restore impaired synaptic connections within the amygdala, and enhanced connectivity with the hippocampus may then "unlock" the memory of the trauma. 38 Furthermore, reduced blood flow in the amygdala may correspond to a decrease in anxiety, 35,39 enabling recipients of MDMA-assisted therapy to face the traumatic memory with less fear.…”
Section: Chemistry and Mechanism Of Actionmentioning
confidence: 99%